Clinical outcomes of combined pars plana vitrectomy and scleral fixation of the intraocular lens with a suspension bridge method in eyes with aphakia or insufficient capsular support. Issue 7 (9th January 2021) - Choi, Hun Jin; Kwon, Oh Woong; Byeon, Suk Ho; Song, Ji Hun
Abstract: Purpose: To describe a modified technique of scleral fixation for intraocular lens (IOL) implantation and report the clinical outcomes of combined pars plana vitrectomy and scleral IOL fixation using the suspension bridge method. Methods: This retrospective case series included 57 eyes (56 patients) of aphakia or phakic and pseudophakic eyes with insufficient capsular support that underwent IOL implantation or dislocated IOL repositioning with scleral fixation using the 'suspension bridge' method by a single surgeon between 1 July 2010 and 1 March 2019. Preoperative status, changes in visual acuity, refractive outcomes as spherical equivalent and related complications were assessed with a minimum follow‐up of 3 months. Results: The mean follow‐up period was 25.5 ± 25.4 months. Preoperative visual acuity (logarithm of the minimum angle of resolution) was 1.32 ± 0.68 (20/400 Snellen), and it significantly improved to 0.80 ± 0.53 (20/125), 0.59 ± 0.56 (20/80) and 0.24 ± 0.37 (20/35) at 1 week, 1 month and 3 months, respectively (p < 0.001). Postoperative complications included corneal wound dehiscence ( n = 1), vitreous incarceration ( n = 1), optic‐iris capture ( n = 6) and cystoid macular oedema ( n = 1). The above‐mentioned complications were successfully corrected with simple procedures. However, one case of IOL dislocation required reoperation. Conclusion: The modified technique of the suspension bridge method precludes the need for a scleral flap, with the advantage of easy adjustment of the IOL position. It is a simple and feasible technique with good surgical results and low complication rates.